2000
DOI: 10.1089/10430340050015905
|View full text |Cite
|
Sign up to set email alerts
|

Development of a Self-Inactivating, Minimal Lentivirus Vector Based on Simian Immunodeficiency Virus

Abstract: In contrast to oncoviruses, lentiviruses do not require target cell division for integration into the host genome. Lentiviral vectors can therefore expand the spectrum of target cells susceptible to retroviral gene transfer. To analyze whether vectors based on simian immunodeficiency viruses (SIVs) could be used for gene transfer, a three-plasmid vector-packaging system was developed, in which Gag-Pol and the vector itself are of SIV origin, while Env is derived either from SIV, amphotropic murine leukemia vir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
103
0
1

Year Published

2000
2000
2015
2015

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 115 publications
(106 citation statements)
references
References 31 publications
2
103
0
1
Order By: Relevance
“…23 Possible strategies to obtain MLV-derived retroviral vectors capable of infecting nondividing cells may therefore consist in the substitution of MLV proteins by the corresponding HIV proteins that permit interaction with the nuclear import machinery 24 or in the introduction of NLS sequences into MLV PIC proteins. As an alternative and more effective strategy, several groups have reported the generation of retroviral vectors derived from lentiviruses such as HIV-1, 25,26 HIV-2, 27 SIV, 28,29 feline immunodeficiency virus, 30 or equine infectious anemia virus. 31,32 The development of lentivirus-based vectors, particularly those derived from HIV-1, is a rapidly progressing field and several studies have demonstrated that these vectors can transduce nondividing cells ex vivo 15,26,33,34 and in vivo.…”
Section: Introductionmentioning
confidence: 99%
“…23 Possible strategies to obtain MLV-derived retroviral vectors capable of infecting nondividing cells may therefore consist in the substitution of MLV proteins by the corresponding HIV proteins that permit interaction with the nuclear import machinery 24 or in the introduction of NLS sequences into MLV PIC proteins. As an alternative and more effective strategy, several groups have reported the generation of retroviral vectors derived from lentiviruses such as HIV-1, 25,26 HIV-2, 27 SIV, 28,29 feline immunodeficiency virus, 30 or equine infectious anemia virus. 31,32 The development of lentivirus-based vectors, particularly those derived from HIV-1, is a rapidly progressing field and several studies have demonstrated that these vectors can transduce nondividing cells ex vivo 15,26,33,34 and in vivo.…”
Section: Introductionmentioning
confidence: 99%
“…The extensive body of knowledge that has been generated on this virus has allowed researchers to reengineer it as a gene vector. HIV-1 remains the best studied vector (Lever et al 2004), although recent work has revealed the potential of HIV-2 (Sadaie et al 1998) SIV (Schnell et al 2000;Stitz et al 2001), EIAV (equine infectious anemia virus) (Olsen 1998;Mitrophanous et al 1999;Ikeda et al 2003) 2002; Loewen et al 2003) and BIV (bovine immunodeficiency virus) (Takahashi et al 2002) as vectors.…”
Section: Lentiviral Vectorsmentioning
confidence: 99%
“…In addition, the U3 region of the 3 -LTR has also been deleted in order to eliminate, in target cells, the risk of promoter interference and susceptible oncogenic derivations. Such LTR-inactive LV vectors, termed selfinactivating (SIN), have largely been generated in HIV-1 [28,29,59,60], SIV [3,61] and EIAV [57] contexts. Although the absence of promoting sequences in the 3 -LTR of the integrated proviral genomes should prevent the potential transcriptional activation of a downstream gene, a recent study has shown high frequencies of transcriptional readthrough of the 3 -polyadenylation signals from the internal promoter of SIN-derived HIV-1 and MLV vectors [62].…”
Section: Incorporation Of Additional Cis-acting Regulatory Sequencesmentioning
confidence: 99%